Culicinae (Diptera: Culicidae) Mosquitoes in Chabahar County, Sistan and Baluchistan Province, Southeastern Iran - SH Moosa-Kazemi; H Vatandoost; H Nikookar; M Fathian (Tehran University of Medical Sciences, 2009)
Background: Mosquito-borne diseases are a major public health threat in Iran. The objective of this study was to determine the fauna of culicinae mosquitoes for future mosquito control programs. Methods: Three genera and eleven species of the subfamily Culicinae (Diptera: Culicidae) were collected by dipping technique and identified in Chabahar County, Sistan and Baluchistan Province, southeastern Iran, during January, February, and March 2007. Results: The collected species included:  Aedes vexans (new occurrence record for the province), Culex  arbieeni, Cx. bitaeniorhynchus, Cx. deserticola, Cx. hortensis, Cx. perexiguus, Cx. pipiens, Cx.  pseudovishnui, Cx. pusillus, Cx. quinquefasciatus, Cx. sinaiticus, Cx. theileri, Cx. tritaeniorhynchus, Culiseta longiareolata, Ochlerotatus caballus, Oc. caspius, and Uranotaenia unguiculata. Conclusion: Our observations indicate that, in South of Iran hot and wet climatic conditions support the persistence of culicinae mosquitoes. As our study, regular monitoring of culicinae mosquitoes in this area could be the most useful for mosquito control and mosquito-borne disease prevention.